Pengaruh Capital Intensity, Inventory Intensity, dan Kepemilikan Asing Terhadap Tax Avoidance - Mutia Safira; Ahalik (UNIVERSITAS KALBIS, 2022)
This study aims to determine whether capital intensity, inventory intensity and foreign ownership effect tax avoidance. The population is manufacturing companies in the basic industrial and chemical sectors which are listed on the Indonesia Stock Exchange (IDX) for the 2016-2018 period. The sample selection method uses purposive sampling totaling 40 companies with 120 observational data. The data analysis method used is multiple linear regression analysis using SPSS version 25 to test whether there is an influence between capital intensity, inventory intensity, and foreign ownership on tax avoidance. The results of the reasearch show that inventory intensity and foreign ownership have a significant effect on tax avoidance, while capital intensity has no effect on tax avoidance.